AFTER EXERCISE TRAINING IN SUBJECTS FOLLOWING MYOCARDIAL INFARCTION - Metelka, Rudolf; Weinbergova, Otilie; Opavsky, Jaroslav; Salinger, Jiri; Ostransky, Jiri (Biomedical papers, 1999)
Heart rate variability reflects the activity of autonomic nervous system. The aim was to evaluate the value ofshort-term spectral analysis of heart rate for monitoring the effects of exercise training on the autonomic nervoussystem in subjects following myocardial infarction. Short-term spectral analysis of heart rate variability wasperformed during standardised supine-standing-supine test in a group of 29 clinically stable patients after myocardialinfarction and the same test was repeated after 2 months of exercise training (ergometry or rapid walking).Each subject exercised at 60-80% of his maximal performance for 30 minutes once a day. Short-term spectralanalysis of heart rate variability was assessed in the frequency range of 0.02-0.5Hz involving very low frequency(VLF, 0.02-0.05Hz), low frequency (LF, 0.05-0.15Hz) and high frequency (HF, 0.15-0.5Hz) spectral bands. Theinfluence of exercise training on the autonomic nervous system was registered in the physically active group (n = 16)as a decrease in sympathetic response to standardised orthostatic load. In conclusions the regular exerciseinfluenced an altered neural autonomic regulation of heart rate in post-infarction patients shown by a decrease insympathetic activity in the short-term heart rate variability. This method enables monitoring of the effects ofphysical training on the autonomic nervous system in patients following myocardial infarction.
Keywords: Spectral analysis / Heart rate variability / Autonomic nervous system / Myocardial infarction / Physical training